Identification of de novo mutations for ARID1B haploinsufficiency associated with Coffin-Siris syndrome 1 in three Chinese families via array-CGH and whole exome sequencing - Guanting Lu; Qiongling Peng; Lianying Wu; Jian Zhang; Liya Ma (BMC, 2021)
Abstract Background Coffin-Siris syndrome (CSS) is a multiple malformation syndrome characterized by intellectual disability associated with coarse facial features, hirsutism, sparse scalp hair, and hypoplastic or absent fifth fingernails or toenails. CSS represents a small group of intellectual disability, and could be caused by at least twelve genes. The genetic background is quite heterogenous, making it difficult for clinicians and genetic consultors to pinpoint the exact disease types. Methods Array-Comparative Genomic Hybridization (array-CGH) and whole exome sequencing (WES) were applied for three trios affected with intellectual disability and clinical features similar with those of Coffin-Siris syndrome. Sanger sequencing was used to verify the detected single-nucleotide variants (SNVs). Results All of the three cases were female with normal karyotypes of 46, XX, born of healthy, non-consanguineous parents. A 6q25 microdeletion (arr[hg19]6q25.3(155,966,487-158,803,979) × 1) (2.84 Mb) (case 1) and two loss-of-function (LoF) mutations of ARID1B [c.2332 + 1G > A in case 2 and c.4741C > T (p.Q1581X) in case 3] were identified. All of the three pathogenic abnormalities were de novo, not inherited from their parents. After comparison of publicly available microdeletions containing ARID1B, four types of microdeletions leading to insufficient production of ARID1B were identified, namely deletions covering the whole region of ARID1B, deletions covering the promoter region, deletions covering the termination region or deletions covering enhancer regions. Conclusion Here we identified de novo ARID1B mutations in three Chinese trios. Four types of microdeletions covering ARID1B were identified. This study broadens current knowledge of ARID1B mutations for clinicians and genetic consultors.